2018
DOI: 10.1021/acs.jmedchem.8b00529
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a Weakly Binding Fragment into a Potent RORγt Inverse Agonist with Efficacy in an in Vivo Inflammation Model

Abstract: The transcription factor RORγt is an attractive drug-target due to its role in the differentiation of IL-17 producing Th17 cells that play a critical role in the etiopathology of several autoimmune diseases. Identification of starting points for RORγt inverse agonists with good properties has been a challenge. We report the identification of a fragment hit and its conversion into a potent inverse agonist through fragment optimization, growing and merging efforts. Further analysis of the binding mode revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Compound 15 was prepared according to the general procedure described for 11. Flash column chromatography eluent: petroleum ether/EtOAc = 5/1; yield, 65%; yellow solid; 1 H NMR (400 MHz, DMSO-d 6 ) δ 10.17 (17). 16 (100 mg, 0.17 mmol) was dissolved in THF (5 mL) and 2 mol/L NaOH aqueous solution (5 mL).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Compound 15 was prepared according to the general procedure described for 11. Flash column chromatography eluent: petroleum ether/EtOAc = 5/1; yield, 65%; yellow solid; 1 H NMR (400 MHz, DMSO-d 6 ) δ 10.17 (17). 16 (100 mg, 0.17 mmol) was dissolved in THF (5 mL) and 2 mol/L NaOH aqueous solution (5 mL).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Efforts to discover orally bioavailable inverse agonists of RORγt, as an alternative to antibody treatment, have generated a variety of different structural classes. Indeed, a diverse range of chemical structures has been reported as RORγt inhibitors by many research groups. Recent clinical candidates from these efforts include VTP-43742, GNE-3500, AZD-0284, GSK805, T0901317, and GSK2981278 (Figure ). Among them, GSK2981278 was developed in a phase II study for the topical treatment of psoriasis, but recently, the clinical development of this compound was halted. GSK2981278 has potent in vitro RORγt inverse agonistic activity in a binding inhibitory assay and in a RORγt reporter gene assay (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Compound 17 was converted to 18 by methylation. The reaction of 18 with (2,4dimethoxyphenyl) methenamine(19) yielded compound 20. Compound 20 was deprotected using trifluoroacetic acid (TFA) to provide 21.…”
mentioning
confidence: 99%
“…In the absence of ligand, RORgt is in an active conformation, capable of recruiting coactivators. From a structural point of view, His 479 , Tyr 502 , and Phe 506 triplets have been identified as the primary structural elements responsible for stabilizing H12 and anchoring RORgt in the active conformation, allowing coactivator interactions (Williams et al, 2003;Carcache et al, 2018;Schnute et al, 2018). Agonist compounds stabilize the active conformation either directly or indirectly and it has been shown that a putative natural ligand like 25-hydroxy-cholesterol stabilizes H12 indirectly through a water-mediated hydrogen bond between His 479 and Tyr 502 Fig.…”
Section: Discussionmentioning
confidence: 99%